PENGEMBANGAN TEKNIK DASAR PERMAINAN BOLA BASKET BERBASIS E-BOOK - Young Sitompul; Arif Ramadani; Ade Irmawan; M.Irfan; Eva Faridah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an e-book learning medium on basic basketball techniques that can be used effectively in the Physical Education, Sports, and Health (PJOK) learning process. The main problem in basketball learning is the limited availability of digital media that can facilitate conceptual understanding through visual, interactive, and independent approaches. The research method used the Research and Development (R&D) model with the ADDIE approach, which includes analysis, design, development, implementation, and evaluation. The research subjects consisted of 22 tenth-grade students from SMK Negeri 1 Percut Sei Tuan and involved subject matter experts, media experts, and language experts as validators. The validation results showed that the E-book received a very feasible rating from all validators, while limited trials showed positive responses and increased student learning activities. This product has been proven effective in improving students' understanding of basic basketball techniques and supporting technology-based independent learning. Thus, this E-book is feasible to be implemented as an alternative innovative learning media in PJOK subjects.